Facile Synthesis of Manganese Tellurite Nanoparticles for Magnetic Resonance Imaging‐Guided Photothermal Therapy. (16th April 2021) - He, Yu; Guo, Yating; Yu, Yanbin; Luo, Peifu; Qiu, Honglong; Huang, Guoming
Abstract: In this study, manganese tellurite (MnTeO3 ) nanoparticles are developed as theranostic agents for magnetic resonance imaging (MRI)‐guided photothermal therapy of tumor. MnTeO3 nanoparticles are synthesized via a simple one‐step method. The as‐synthesized MnTeO3 nanoparticles with uniform size show good biocompatibility. In particular, MnTeO3 nanoparticles exhibit a high photothermal conversion efficiency (η = 26.3%), which is higher than that of gold nanorods. Moreover, MnTeO3 nanoparticles also have high MRI performance. The longitudinal relaxivity ( r 1 ) value of MnTeO3 nanoparticles is determined to be 8.08 ± 0.2 mm −1 s −1, which is higher than that of clinically approved T 1 ‐contrast agents Gd‐DTPA (4.49 ± 0.1 mm −1 s −1 ). The subsequent MnTeO3 nanoparticles‐mediated photothermal therapy displays a highly efficient ablation of tumor cells both in vitro and in vivo with negligible toxicity. It is demonstrated that MnTeO3 nanoparticles can serve as promising theranostic agents with great potentials for MRI‐guided photothermal therapy. Abstract : Manganese tellurite (MnTeO3 ) nanoparticles are synthesized and used as a promising nanoplatform for cancer theranostics combining MRI diagnosis and efficient photothermal therapy.